2009
DOI: 10.1111/j.1530-0277.2009.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Mouse Embryonic Stem Cells

Abstract: Our findings suggest that ethanol may contribute to the pathogenesis of FAS by triggering apoptotic pathways during differentiation of embryonic stem cells and deregulating early stages of embryogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 71 publications
5
48
1
Order By: Relevance
“…We demonstrated earlier that the expression of Sox2, Oct4, and Nanog in the EB cell lysates was elevated with ethanol (100 mM) exposure [5]. However, the complexity of the multilineage EB cell aggregates and their interactions [55] does not facilitate a systematic analysis of the role of ethanol in the regulation of transcription factors along a single lineage.…”
Section: Ethanol Regulates the Expression Of Oct4 In Early Es Cell DImentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated earlier that the expression of Sox2, Oct4, and Nanog in the EB cell lysates was elevated with ethanol (100 mM) exposure [5]. However, the complexity of the multilineage EB cell aggregates and their interactions [55] does not facilitate a systematic analysis of the role of ethanol in the regulation of transcription factors along a single lineage.…”
Section: Ethanol Regulates the Expression Of Oct4 In Early Es Cell DImentioning
confidence: 99%
“…However, the earlier developmental stages and interference of ethanol with regulation of core transcription factors have not been elucidated. In our earlier study [5], we investigated the changes of Sox2, Oct4, and Nanog with ethanol during mouse ES cell spontaneous differentiation in suspension to the EBs. We demonstrated that downregulation of these transcription factors was not completed within 6 days in the presence of 100 mM ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a critical role for ethanol in promoting apoptotic events in various cell lines and animal models has been well documented. [20][21][22][23][24][25][26][27][28][29] Also, ethanol stimulates the TRAIL-induced apoptosis in leukemic T-lymphocytes and colon cancer cells in vitro. 38,39 Despite these data, an interactive effect of ethanol and TRAIL in promoting PCa cell death has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Ethanol-induced apoptotic cell death has been well recognized in many cell types and animal models. [20][21][22][23][24] High concentrations of ethanol can effectively destroy hepatoma tumor as well as normal cells, whereas lower concentrations of ethanol selectively induces apoptosis in hepatoma tumor cells but not in normal hepatocytes. 25 Ethanol induces significant apoptosis of purkinje cells in the developing cerebellum.…”
Section: Introductionmentioning
confidence: 99%